Combined associations of vitamin D and cognitive function with all-cause mortality among older adults in Chinese longevity areas: A prospective cohort study - Dai, Miao; Song, Quhong; Wang, Xiang; Li, Ying; Lin, Taiping; Liang, Rui; Jiang, Tingting; Shu, Xiaoyu; Ge, Ning; Yue, Jirong (Frontiers in Public Health, 2023)
Objectives While both vitamin D deficiency and cognitive impairment have individually been linked to a greater risk of all-cause mortality, the combined effects of these two different conditions have not previously been explored in this context. We aimed to investigate the combined impact of vitamin D concentration and cognitive impairment on all-cause mortality in older adults. Methods The analyzed data were collected from community-dwelling adults ≥ 65 years of age that were enrolled in the Chinese Longitudinal Healthy Longevity Survey (n=1,673). The Mini-Mental Status Examination (MMSE) was used to assess cognitive function, while the plasma 25-hydroxyvitamin D [25(OH)D] test was used to assess vitamin D status. The associations between vitamin D concentration, cognitive function, and all-cause mortality were assessed with Cox proportional hazards models. We used restricted cubic splines to examine the dose-response relationship between vitamin D and the risk of all-cause mortality and used joint effect testing to explore interactions between vitamin D concentration and cognitive function. Results During a mean (SD) follow-up of 3.8 (1.9) years, 899 (53.7%) deaths occurred. A negative dose-response relationship was observed between 25(OH)D concentration and cognition impairment at baseline, as well as the odds of all-cause mortality during follow-up. Similarly, cognitive impairment was significantly related to all-cause mortality risk (HR 1.81, 95% CI: 1.54 to 2.12). The combined analyses showed positive associations, with the highest mortality risk observed in older adults with both low vitamin D and cognitive impairment (HR 3.04, 95% CI: 2.40 to 3.86). Moreover, the interaction between 25(OH)D concentration and cognitive function was found to be significant in relation to the risk of mortality (P for interaction < 0.001). Conclusions Lower plasma 25(OH)D and cognitive impairment were, respectively, associated with increased all-cause mortality risks. The 25(OH)D concentration and cognitive impairment exhibited a combined additive effect on all-cause mortality among older Chinese adults.